Osmotic dehydration process for low temperature blanched pumpkin - Silva, Keila de Souza [UNESP]; Caetano, Lidimara Cassia [UNESP]; Garcia, Carolina Castilho [UNESP]; Romero, Javier Telis [UNESP]; Santos, Adriana Barbosa [UNESP]; Mauro, Maria Aparecida [UNESP] (Elsevier B.V., 2011)
This study investigated the influence of stepwise blanching over the kinetics of osmotic dehydration process and over the physical characteristics of pumpkin (Cucurbita moschata). The 2(3) factorial design and response surface methodology was used to optimize the blanching process. The independent variables for blanching were temperature, blanching time and holding time. These independent variables showed different effects on the two studied answers: texture and color. The kinetics of osmotic dehydration were investigated using 50% and 65% sucrose solutions, using samples previously blanched by both stepwise and conventional means. The diffusivity values for the water and sucrose were similar for the two components, showing greater gains of solute than loss of water in many samples. Blanching affected the color of the pumpkin, whereas osmotic dehydration did not change it significantly. The impregnation process maintained or even increased the tissue firmness when compared to the blanched samples. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Low temperature blanching; Pumpkin; Osmotic dehydration; Response surface; Optimization